Persepsi Mahasiswa Akuntansi Terhadap Etika Pendidik Dengan Kecerdasan Spiritual Sebagai Variabel Intervening (Studi Kasus Pada Universitas Sumatera Utara, Universitasnegeri Medan, Universitas Harapan Medan Dan Universitas Medan Area) - Ayunda Primadani (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
The purpose of this study was to examine the effect of student perceptions on the ethics of educators with spiritual intelligence as an intervening variable. The population in this study were students of the Faculty of Economics majoring in accounting from state universities and private universities in the city of Medan. USU State Universities and UNIMED are currently in the process of Private Universities UNHar and UMA. The sampling technique used probability sampling techniques: simple random sampling, the calculation of the sample size used the Slovin formula with a total population of 370 students and a total sample of 79 respondents was obtained.The data testing technique used Pearson's Correlation Product Moment technique for validity testing, Cronbach's Alpha method for reliability testing, and the One-Sample Kolmogorov-Smirnov Test for normality testing. The hypothesis testing technique uses the Path Analysis test which is carried out with the help of the SPSS for Windows release 26.00 program.The dependent variable (Y) of this study is the ethics of educators. The independent variable (X) student perceptions and for the intervening variable (Z) is spiritual intelligence. This research method is a quantitative research method. For data analysis methods using path analysis test (path analysis). The results showed that: (1) The perceptions of state university students had no positive and insignificant effect on the ethics of educators as indicated by the value of t -0.157 and sig 0.877. (2) Students' perceptions of private tertiary institutions do not have a positive and significant effect on educator ethics as indicated by the t-value of - 2.617 and sig 0.014. (3) Student perceptions of state and private universities have no positive and insignificant effect on spiritual intelligence as indicated by the t- values of -0.157 and -2.487 with sig 0.493 and 0.436. (4) Spiritual intelligence has no positive and insignificant effect on the ethics of educators as indicated by the value of t -1.292 and sig 0.208. (5) Students' perceptions have no positive and insignificant effect on the ethics of educators with spiritual intelligence as an intervening variable indicated by the value of t -0.122 and sig -0.003 and -0.045. Keywords: Student Perception, Spiritual Intelligence, and Educator Ethics